Development of Teaching Modules Based on Technological Pedagogical Content Knowledge and Culturally Responsive Transformative Teaching on the Topic of Chemical Bonding - Lestari, Irma Rahayu; Muntari, Muntari; Mutiah, Mutiah (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2025)
This research aimed to produce feasible and practical teaching modules on grade X chemical bonding topic based on Technological Pedagogical Content Knowledge (TPACK) and Culturally Responsive Transformative Teaching (CRTT). It is a Research and Development (R&D) using the five-step Borg and Gall model. 36 students from class X at SMAN 1 Narmada participated in this studyâ€™s limited trial. Data collection techniques used validation instruments and practicality questionnaires. Aikenâ€™s V index which measures the validity of six aspects including aspects of content feasibility, aspects of suitability for the learning model, aspects of cultural suitability, language, assessment, and completeness of attachments, obtained an average value of V = 0,89 which indicates that the TPACK and CRTT-based teaching module is classified as very valid. The feasibility of the validation results of the teaching module includes six aspects of assessment, with the acquisition of scores in each aspect including; the aspects of content eligibility, suitability with the learning model, cultural suitability, language, assessment, and completeness of attachments obtained an average score of 0.95 consecutively; 0,83; 0,91; 0,83; 0,83; and 1.00. Meanwhile, the practicality test of teaching modules based on teacher responses on the aspects of ease, practicality, attractiveness and benefits of teaching obtained an average practicality of 90% classified as very practical, with four aspects of assessment by teachers, namely ease of use, practicality, attractiveness, and benefits that obtained an average score of 84%; 92%; 92%; and 93%Â respectively. Studentsâ€™ responses on the aspects of presentation, ease of use and benefits of learning devices obtained an average practicality of 83% classified as practical, with an assessment of three aspects, namely media presentation, ease of use of media, and benefits, the average practicality of each was 83%; 82%; and 84%. Thus, it can be concluded that the TPACK and CRTT-based teaching module on the topic of chemical bonding class X SMAN developed is feasible to use in terms of validity and practicality. TPACK and CRTT-based development research is more carried out on the development of e-modules, LKPD for students has not developed many TPACK-based and CRTT-based teaching modules. In addition, previous research has integrated PBL, discovery learning, and PjBL models in developing a teaching material on chemical equilibrium, colloid, and others using 4D and ADDIE development models.